Analisis Penilaian Kinerja Keuangan Menggunakan Metode Rgec Pada Bank Swasta Periode 2020-2022 - Oktarina, Hani; Merina, Citra Indah (CV. ITTC INDONESIA, 2024)
This research aims to assess the financial performance of national private commercial banks during the 2020-2022 period using the RGEC method, which includes Risk Profile, Good Corporate Governance (GCG), Financial Performance and Capital. Evaluation of bank health is carried out through financial ratios: NPL and LDR for Risk Profile, self-assessment for GCG, ROA, ROE, NIM, and BOPO for Financial Performance, and CAR for Capital. Research findings show that in 2020, these banks were categorized as